2022
DOI: 10.1016/j.esmoop.2021.100333
|View full text |Cite
|
Sign up to set email alerts
|

Final efficacy and safety data, and exploratory molecular profiling from the phase III ALUR study of alectinib versus chemotherapy in crizotinib-pretreated ALK-positive non-small-cell lung cancer

Abstract: Background At the primary data cut-off, the ALUR study demonstrated significantly improved progression-free survival (PFS) and central nervous system (CNS) objective response rate (ORR) with alectinib versus chemotherapy in pretreated, advanced anaplastic lymphoma kinase ( ALK )-positive non-small-cell lung cancer. We report final efficacy and safety data, and exploratory molecular profiling. Patients and methods Patients who received prior pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…Our literature search yielded a total of 1798 articles, of which 1680 were excluded after the initial screening of abstracts or titles (Figure 1). After screening and assessing eligibility, 26 studies, which included 31 cohorts, were selected 6,9,10,12,14–16,21–39 …”
Section: Resultsmentioning
confidence: 99%
“…Our literature search yielded a total of 1798 articles, of which 1680 were excluded after the initial screening of abstracts or titles (Figure 1). After screening and assessing eligibility, 26 studies, which included 31 cohorts, were selected 6,9,10,12,14–16,21–39 …”
Section: Resultsmentioning
confidence: 99%
“…For conteltinib, iORR was 33.3% in six patients with measurable intracranial lesions [ 12 ]. Intracranial CR rate was 7% for iruplinalkib, numerically similar to ceritinib (8.7%) [ 17 ], alectinib (8.3%) [ 18 ], and brigatinib 90 mg (8%) [ 10 ]. However, no intracranial CR was reported in the brigatinib 180 mg [ 10 ].…”
Section: Discussionmentioning
confidence: 96%
“…Targeted therapy is playing a significant role in the treatment of lung cancer, but drug resistance is inescapable which is more intractable and intensifies the psychological burden on patients ( 21 , 22 ). In crizotinib-resistant cases, patient switched to alectinib observed a 55% overall response rate ( 23 , 24 ). Two studies reported that patients who are resistant to crizotinib as the first-line treatment achieved significant PFS when they were switched to aletinib.…”
Section: Discussionmentioning
confidence: 99%